2013
DOI: 10.1242/dev.093906
|View full text |Cite
|
Sign up to set email alerts
|

Tendon-bone attachment unit is formed modularly by a distinct pool of Scx- and Sox9-positive progenitors

Abstract: SUMMARYThe assembly of the musculoskeletal system requires the formation of an attachment unit between a bone and a tendon. Tendons are often inserted into bone eminences, superstructures that improve the mechanical resilience of the attachment of muscles to the skeleton and facilitate movement. Despite their functional importance, little is known about the development of bone eminences and attachment units. Here, we show that bone eminence cells are descendants of a unique set of progenitors and that superstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
332
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 246 publications
(364 citation statements)
references
References 37 publications
18
332
1
Order By: Relevance
“…Cre deleter, which labels all cartilage cells as well as a subset of tendon cells (Blitz et al, 2013;Soeda et al, 2010;Sugimoto et al, 2013), we indeed identified a cell lineage boundary at the MP level of the FDS Individual tendons in I can be identified using the schematic and numerical assignments in Fig. 1. tendons.…”
Section: Development Of Fds Tendons Is Also Modular With a Demarcatiomentioning
confidence: 62%
See 3 more Smart Citations
“…Cre deleter, which labels all cartilage cells as well as a subset of tendon cells (Blitz et al, 2013;Soeda et al, 2010;Sugimoto et al, 2013), we indeed identified a cell lineage boundary at the MP level of the FDS Individual tendons in I can be identified using the schematic and numerical assignments in Fig. 1. tendons.…”
Section: Development Of Fds Tendons Is Also Modular With a Demarcatiomentioning
confidence: 62%
“…A few studies have suggested that the tendon and cartilage cell fates represent alternative lineages derived from a common tendo-chondro progenitor population and that inhibition of chondrogenesis may drive these progenitors toward a tendon cell fate (Brent et al, 2003(Brent et al, , 2005Lorda-Diez et al, 2009). This assertion was also supported by recent data showing that the tendon and cartilage cells comprising the entheses, which are the skeletal insertions of tendons, are derived from a pool of Sox9 and Scx co-expressing progenitors that then differentiate toward their respective lineages (Blitz et al, 2013;Sugimoto et al, 2013). There is, however, also some evidence that cartilage may play a direct role in tendon induction.…”
Section: Introductionmentioning
confidence: 58%
See 2 more Smart Citations
“…Ablation of the TGFBR2 gene induces loss of tendon/ligament formation [9,10]. Further research has shown that TGF-β-type-2(TGFBR2) singling plays an essential role for tendon morphogenesis via regulating scleraxis (SCX), which is expressed in all the cells of tendon tissues as a key transcription factor for tenogenic differentiation [11]. TGFBR2 expressing progenitor cells are maintained in postnatal tendonbone junctions [8].…”
Section: Introductionmentioning
confidence: 99%